2017
DOI: 10.1103/physreva.95.042102
|View full text |Cite
|
Sign up to set email alerts
|

Spin-one-half particles in strong electromagnetic fields: Spin effects and radiation reaction

Abstract: Various classical models of electrons including their spin degrees of freedom are commonly applied to describe the electron dynamics in strong electromagnetic fields. We demonstrate that different models can lead to different or even contradicting predictions regarding how the spin degree of freedom modifies the electron's orbital motion when the electron moves in strong electromagnetic fields. This discrepancy is rooted in the model-specific energy dependency of the spin-induced Stern-Gerlach force acting on … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 94 publications
1
50
0
Order By: Relevance
“…The spin-dependent spectrum of an electron in (anti-)parallel state given by equation (3) is consistent the results from the well-known Sokolov-Ternov equation in equation (2). The radiation probability can also be classified to spin-flip case…”
Section: Qed Spin-dependent Radiation-reaction Modelsupporting
confidence: 84%
See 2 more Smart Citations
“…The spin-dependent spectrum of an electron in (anti-)parallel state given by equation (3) is consistent the results from the well-known Sokolov-Ternov equation in equation (2). The radiation probability can also be classified to spin-flip case…”
Section: Qed Spin-dependent Radiation-reaction Modelsupporting
confidence: 84%
“…Therefore it is a promising driver to trigger the spin effect on particle dynamics. Previous studies have shown that by colliding ∼10 1 MeV electrons with a laser of ∼10 22 W cm −2 , electrons with spin up/ down can be deflected to an angle of ±10 −7 rad by the SG force [2]. In the regime where SG effect emerges during collision, it is expected that other exotic phenomena become significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Near equilibrium the entropy production is just quadratic in the current, but that may change drastically farther from equilibrium. That appears again in recent studies of thermodynamic uncertainty relations [70][71][72][73][74][75], concentrating on lower bounds for the entropy production rate and giving interesting refinements to the positivity of entropy production or to Carnot efficiency, see [76] and references therein, in particular [40] for an interpretation of lower bounds on the dissipation rate. One should not forget that quadratic lower bounds for the dissipation rate, in terms of currents, are not at all sharp in the nonlinear force-current regimes.…”
Section: Discussion On Nondissipative Effectsmentioning
confidence: 97%
“…Unfortunately, the generalization of relativistic quantum description for particles with anomalous magnetic moment is still not clear [17]. An overview of these approaches and their numerical tests can be found in [18,19]. Our model [1] expands on the pioneering work of the first formulations.…”
Section: Introductionmentioning
confidence: 99%